Faktor-Faktor Penyebab Klaim Tertunda BPJS Kesehatan RSUD Dr. Kanujoso Djatiwibowo Periode Januari – Maret 2016 - EP, Antonius Artanto (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2018)
There was 10-15% pending of claim because uncomplete medic in Dr. Kanujoso Djatiwiwo Hospital. The purpose of this study is to find factors affecting pending of claims of Badan Penyelenggara Jaminan Sosial Kesehatan as claims guidance and contract paper. Data sources has taken from pending of claims of dr Kanujoso Djatiwibowo hospital periode January – March 2016 and see the deeper problem behind this problems through informans. This study is quantitative qualitative research with analitic describtion method with retrospective study from pending of claims, interview and discussion. The result from this study shows factor affecting pending of claims is the absence ofspecialist doctor who responsible for the patien because there is double function from case manager that effect delaying completing electronic medical resume. Suggest to use immediately electronic medical record, splitting job for case manager and doctor on ward, increasing obedience to write patien data from beginning such as performance evaluation and integrated remuneration.